2018
DOI: 10.1016/j.bbmt.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Stem Cell Transplantation for Patients with Early Progression of Follicular Lymphoma: A Follow-Up Study of 2 Randomized Trials from the German Low Grade Lymphoma Study Group

Abstract: Patients with follicular lymphoma (FL) and progression of disease (POD) within 24 months after frontline treatment (POD24) have poor overall survival (OS). The optimal salvage treatment for these patients is unknown. We assessed the role of high-dose therapy and autologous stem cell transplantation (ASCT) in transplant-eligible patients. We analyzed 162 patients with advanced-stage FL who had received frontline treatment within the GLSG1996 or GLSG2000 trials. All patients had POD at age ≤ 65 years and had not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 34 publications
0
42
0
1
Order By: Relevance
“…It too confirmed that ASCT resulted in significantly higher 5-year OS compared with not receiving ASCT (77% vs 46%). 37 Use of sibling-matched (MSD) or unrelated-donor allogeneic transplantation has also been studied but has expected toxicity. The CIBMTR separately evaluated unrelated-donor and MSD transplantation compared with ASCT in FL patients with POD24 or refractory disease.…”
Section: Is the Patient A Candidate For A Clinical Trial?mentioning
confidence: 99%
“…It too confirmed that ASCT resulted in significantly higher 5-year OS compared with not receiving ASCT (77% vs 46%). 37 Use of sibling-matched (MSD) or unrelated-donor allogeneic transplantation has also been studied but has expected toxicity. The CIBMTR separately evaluated unrelated-donor and MSD transplantation compared with ASCT in FL patients with POD24 or refractory disease.…”
Section: Is the Patient A Candidate For A Clinical Trial?mentioning
confidence: 99%
“…Carmustine, etoposide, cytarabine, melphalan (BEAM) is the dominant conditioning regimen used (1808/3196 patients [56·6%] in the studies outlined; Table I). 1,100–104,113–116,121 Transplant‐related, non‐relapse mortality (NRM) is typically low, with 100‐day NRM of 1–2% and 1–3‐year NRM of approximately 3%. TBI‐based conditioning is associated with a higher NRM and a concerning 8–12% rate of secondary myeloid malignancies 1,100 .…”
Section: Transplantation In Flmentioning
confidence: 99%
“…Few prospective data are available regarding HSCT in the era of modern therapies, and its role continues to be elucidated . Retrospective data suggest that patients with POD24 benefit from auto‐HSCT (i.e., increased PFS and OS compared with those not receiving transplant) . A recent study compared auto‐HSCT with either matched‐sibling donor (MSD) or unrelated matched donor (UMD) allogeneic HSCT (allo‐HSCT) in patients with POD24 .…”
Section: Fl Treatmentmentioning
confidence: 99%